Hubungan Kebiasaan Sarapan Pagi Dengan Tingkat Konsentrasi Belajar Pada Anak Sekolah Dasar Di Sdn 66 Kota Bengkulu - Inda Andreani; Retni Retni; Meri Epriana Susanti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
In Indonesia, based on data from the 2018 Basic Health Research (Riskesdas), approximately 44.6% of children aged 6–12 years do not have a good breakfast habit. This is concerning, as breakfast contributes 15–30% of daily energy needs. The objective of this study was to determine the relationship between breakfast habits and learning concentration among elementary school students at SDN 66 Bengkulu City.The research employed a descriptive method with a cross-sectional approach. The sampling technique used was Purposive Sampling, with a total of 56 students from SDN 66 Bengkulu City participating as samples.Univariate analysis showed that almost half of the respondents (37.5%) did not have breakfast, and a similar proportion (39.3%) had poor learning concentration. The results of the bivariate analysis revealed a significant relationship between breakfast habits and learning concentration in elementary school students at SDN 66 Bengkulu City in 2025 (p-value 0.000).The researcher suggests that respondents should make it a habit to always eat breakfast before going to school, as this is crucial for maintaining energy, concentration, and readiness to learn.